Development of an Open Source Hourly Building Energy Modeling Software Tool - Hanam, Brittany (University of Waterloo, 2010)
Computer building energy simulations are an important tool in the design of low-energy buildings. Building energy modeling is used to predict annual energy consumption, determine peak loads for sizing equipment, complete cost-payback analysis to select appropriate energy efficiency measures, and show compliance with standards. While energy modeling is a cost effective tool to assist in design, there are a number of challenges in the current building energy modeling industry. Most energy modeling programs are too technical to be used by architects, and too complex for early design when many system parameters are not known. Programs that are easy to use lack accuracy and the ability to model new, innovative systems. Programs that allow the simulation of new systems are very complex and have a high learning curve for engineers. In this thesis, a computer program that was developed to model building energy loads and energy consumption of mechanical systems is presented. The program, entitled “Building Energy and Loads Analysis” (BELA), has a transparent, open architecture to allow additions and changes, and it facilitates the simulation of simple early design and detailed later design. BELA is currently a simple, single-zone model but it could be expanded at a later date. The program consists of two stages: the loads model and the systems model. In the loads model, users define a building through a series of inputs. The program uses these inputs to calculate the total heat transfer acting on the space, which is the total heating or cooling load on the space. The systems model calculates the total energy consumption of the building. These calculations are performed hourly for one year. Two heating and cooling systems models have been created, radiant heating and cooling, and fan coil units, both with a dedicated outdoor air system to provide ventilation. The output of the loads model can be used to view the loads on the buildings, and to view how enclosure design parameters such as amount of insulation or type of window affect the building loads. The output of the systems model shows the total energy consumption of the building for one year. It can be used to compare different mechanical systems and evaluate various design parameters within the systems. The BELA program is used to create a natural ventilation model in order to demonstrate the implementation of an innovative system, and to compare the energy consumption of a naturally ventilated building to a mechanically ventilated building. The case study model showed that natural or hybrid ventilation can reduce building energy consumption when designed properly, however when used incorrectly it can significantly increase energy consumption. For scenarios where opening sizes were not restricted to provide only the necessary airflow, energy consumption of natural ventilation was higher than with the dedicated outdoor air system. This was due to the increased space heating and cooling loads from excessive unconditioned air entering the building. When opening sizes were limited to provide only the required airflow rates and to take advantage of free cooling, energy consumption for a year was reduced by 3.5%. This simulation showed that natural ventilation may save a small amount of energy when designed correctly. However, designers should evaluate it concurrently with other energy efficiency measures that may provide greater energy savings.
Keywords: building; energy; Civil Engineering